Dakwah Rohana Kuddus Dalam Surat Kabar Soenting Melajoe Tahun 1912-1921 - Farah Hanifah; Nirwan Syafrin; Dewi Anggrayni (Dakwatussifa: Journal of Da'wah and Communication, 2022)
Da'wah is an obligation for every Muslim, as Allah sent His Prophets and Messengers to spread the message of da'wah to all corners of the earth. The man was created as a caliph or leader on earth, with the aim of always worshiping Him. Da'wah is an invitation, a call, a call for humans to the way of Allah. Talking about da'wah, the context is not only always delivered by lecture, or verbal delivery, but can be in written form. Along with the times, technology and information media have also developed. Da'wah must always develop in conveying it, one of which is through the mass media. The media has the power to lead public opinion, especially Muslims who make up the largest population in Indonesia. The press itself had developed in Minangkabau at the beginning of the 20th century as a forum for information from various fields, social, political, economic, and cultural which at that time were so dynamic. This great opportunity was also taken by the pioneering female figure of the National press, Rohana Kuddus. The movement of Rohana Kuddus in writing, especially in journalism, as well as being the first female journalist in Indonesia, is so massive to voice women's rights. Rohana Kuddus used her pen as a weapon against injustice as well as a form of defense against women who were still very limited at that time. So Rohana Kuddus used da'wah through writing which was realized by establishing the first newspaper which was managed directly by women as a forum for expressing thoughts, implying a fighting spirit, as well as special da'wah messages for women. Rohana Kuddus was determined to establish the first women's newspaper in Indonesia, Soenting Melajoe, assisted by Datuk Sutan Maharadja, which was published in 1912-1921. Keywords: Da’wah, Rohana Kuddus, Soenting Melajoe